Intra-Hospital Commission for Organ and Tissue Donation for Transplants: the barriers encountered by health workers (Research, Society and Development, 2022)
Objective: to identify the barriers encountered by health workers of an Intra-Hospital Commission for Donation of Organs and Tissues for Transplants during the process of donating organs and tissues for transplants. Methodology: qualitative research, through interviews with twenty workers of an Intra-Hospital Commission for the Donation of Organs and Tissues for Transplants, applying the technique of Discursive Textual Analysis. Results: feelings of frustration and disappointment were evidenced in the face of family denial; the lack and failure of communication and interest by some workers working directly in the care of the potential donor in opening the Brain Death Protocol; the lack of availability of the neurologist and anesthesiologist for organ harvesting; the distance of the study city in relation to the capture team's city; deficiency of trained workers, in addition to facing difficult moments experienced among themselves and with the potential donor's family. Conclusion: the results suggest the importance of implementing strategies with the objective of attributing more social value and raising awareness of the population about donation, in addition to more qualified health workers to work together with members of the organ and tissue donation team for transplants.